2008
DOI: 10.1111/j.1365-313x.2008.03653.x
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of the explosive 2,4,6‐trinitrotoluene in Arabidopsis: discovery of bifunctional O‐ and C‐glucosyltransferases

Abstract: SummaryPlants, as predominantly sessile organisms, have evolved complex detoxification pathways to deal with a diverse range of toxic chemicals. The elasticity of this stress response system additionally enables them to tackle relatively recently produced, novel, synthetic pollutants. One such compound is the explosive 2,4,6-trinitrotoluene (TNT). Large areas of soil and groundwater are contaminated with TNT, which is both highly toxic and recalcitrant to degradation, and persists in the environment for decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
117
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 37 publications
2
117
0
Order By: Relevance
“…While the ability to conjugate these synthetic compounds is not the endogenous role of t class GSTs, it is possible that these xenobiotics might share chemical similarities with endogenous substrates. Gandia-Herrero et al, 2008) and corroborative qPCR data on Arabidopsis plants treated with TNT. The qPCR results were normalized to the ACTIN2 gene, and the results are means of five biological replicates 6 SE.…”
Section: Activity Of Recombinant Gstsmentioning
confidence: 71%
See 4 more Smart Citations
“…While the ability to conjugate these synthetic compounds is not the endogenous role of t class GSTs, it is possible that these xenobiotics might share chemical similarities with endogenous substrates. Gandia-Herrero et al, 2008) and corroborative qPCR data on Arabidopsis plants treated with TNT. The qPCR results were normalized to the ACTIN2 gene, and the results are means of five biological replicates 6 SE.…”
Section: Activity Of Recombinant Gstsmentioning
confidence: 71%
“…Following production, GST conjugates are imported to the vacuole, and two glutathione conjugate ATP-binding cassette transporters, Multidrug resistance-associated protein1 (MRP1) and MRP2, are up-regulated in Arabidopsis in response to TNT (2-and 5-fold respectively; Gandia-Herrero et al, 2008). After import, studies on herbicide detoxification by GSTs showed that further processing occurs, releasing cysteinyl-Gly, g-glutamyl-Cys, and Cys derivatives (Grzam et al, 2006; Ohkama-Ohtsu Table II.…”
Section: Glutathione-tnt Productsmentioning
confidence: 99%
See 3 more Smart Citations